A detailed analysis of methylmalonic acid kinetics during hemodialysis and after combined liver/kidney transplantation in a patient with mut0 methylmalonic acidemia. Issue 6 (25th June 2014) - Vernon, Hilary J.; Sperati, C. John; King, Joshua D.; Poretti, Andrea; Miller, Neil R.; Sloan, Jennifer L.; Cameron, Andrew M.; Myers, Donna; Venditti, Charles P.; Valle, David
Abstract: End stage kidney disease is a well‐known complication of methylmalonic acidemia (MMA), and can be treated by dialysis, kidney transplant, or combined kidney‐liver transplant. While liver and/or kidney transplantation in MMA may reduce the risk of metabolic crisis and end‐organ disease, it does not fully prevent disease‐related complications. We performed detailed metabolite and kinetic analyses in a 28‐year‐old patient with mut 0 MMA who underwent hemodialysis for 6 months prior to receiving a combined liver/kidney transplant. A single hemodialysis session led to a 54 % reduction in plasma methylmalonic acid and yielded a plasma clearance of 103 ml/min and VD 0.48 L/kg, which approximates the total body free water space. This was followed by rapid reaccumulation of methylmalonic acid over 24 h to the predialysis concentration in the plasma. Following combined liver/kidney transplantation, the plasma methylmalonic acid was reduced to 3 % of pre‐dialysis levels (6, 965 ± 1, 638 (SD) μmol/L and 234 ± 100 (SD) μmol/L) but remained >850× higher than the upper limit of normal (0.27 ± 0.08 (SD) μmol/L). Despite substantial post‐operative metabolic improvement, the patient developed significant neurologic complications including acute worsening of vision in the setting of pre‐existing bilateral optic neuropathy, generalized seizures, and a transient, focal leukoencephalopathy. Plasma methylmalonic acid was stable throughout the post‐operative course. The biochemical parameters exhibited by this patient further define the whole body metabolism of methylmalonic acid in the setting of dialysis and subsequent combined liver/kidney transplant.